Influence of paid maternity leave on return to work after childbirth - Vargas-Prada, Sergio; García, Ana Maria; Ronda, Elena; Estarlich, Marisa; Ballester, Ferran; Benavides, Fernando G. (La Medicina del Lavoro, 2018)
Background: Paid maternity leave (ML) has been associated with better health outcomes in mothers and newborns. However, its protective role in mothers’ employment after childbirth remains unclear. Objective: To assess the association between paid ML and being employed 1-year after childbirth. Methods: As part of the INfancia y Medio Ambiente (INMA) cohort study, 507 Spanish women employed at 12th week of pregnancy, were asked about their employment status and job characteristics at 32nd week of pregnancy. One year after childbirth, they were re-interviewed about their employment status and if they had taken paid ML. Incidence of maternal employment 1-year after childbirth was estimated. Crude and adjusted associations with paid ML were assessed by logistic regression, and characterized by odds ratios (ORs) with associated 95% CIs. Results: Information was obtained from 398 women. Of those, 290 (72.9%) were employed 1-year after childbirth. Incidence of maternal employment was lower for those who: i) didn’t take paid ML, ii) were younger than 27 years; iii) had temporary contract, iv) had part-time jobs, v) reported less-favoured familiar social class, and vi) left the job before 32 weeks of pregnancy. Being employed 1-year after childbirth was more common in those who took paid ML (OR 2.7, 95%CI 1.6-4.5), also after adjusting for staying at work until advanced stages of pregnancy (OR 1.8, 95%CI 1.0-3.1). Conclusions: Taking paid ML seems to be associated with higher maternal employment rates 1-year after childbirth. Therefore, our findings suggest that protection of maternity might positively influence women’s labour market participation after childbirth.